2012
DOI: 10.1111/j.1574-6968.2012.02627.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of polymorphic microsatellite markers issued from pyrosequencing technology for the medicinal mushroom Agaricus subrufescens

Abstract: The recently described procedure of microsatellite-enriched library pyrosequencing was used to isolate microsatellite loci in the gourmet and medicinal mushroom Agaricus subrufescens. Three hundred and five candidate loci containing at least one simple sequence repeats (SSR) locus and for which primers design was successful, were obtained. From a subset of 95 loci, 35 operational and polymorphic SSR markers were developed and characterized on a sample of 14 A. subrufescens genotypes from diverse origins. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For each SSI, the level of ploidy ( n + n vs. n ) was determined with a multilocus genotype test based on 21 genomic microsatellite markers (hereinafter referred to as SubSSR for A . Sub rufescens simple sequence repeats) ( Foulongne-Oriol et al 2012c ) that showed polymorphism between the two parental homokaryons: SSIs that did not exhibit heteromorphic profile at any loci were considered homokaryotic ( Thongklang et al 2014a ). Among the 380 SSIs tested, 79 were found homokaryotic and were thus selected for further mapping purposes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each SSI, the level of ploidy ( n + n vs. n ) was determined with a multilocus genotype test based on 21 genomic microsatellite markers (hereinafter referred to as SubSSR for A . Sub rufescens simple sequence repeats) ( Foulongne-Oriol et al 2012c ) that showed polymorphism between the two parental homokaryons: SSIs that did not exhibit heteromorphic profile at any loci were considered homokaryotic ( Thongklang et al 2014a ). Among the 380 SSIs tested, 79 were found homokaryotic and were thus selected for further mapping purposes.…”
Section: Methodsmentioning
confidence: 99%
“…The genotyping of genomic SubSSR markers ( Foulongne-Oriol et al 2012c ) followed from the homokaryon selection test described above. In addition to this first set of 21 microsatellite markers, EST-SSRs (hereinafter referred to as ES-SSR) were also used for mapping ( Foulongne-Oriol et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CA646 and CA647 are two cultivars sold in Europe by Mycelia (Belgium) under the reference numbers 7700 and 7703, respectively. CA560 was isolated in Botucatu, Brazil (1999) from a commercial farm and CA572 is a Brazilian cultivar purchased by D.C. Zied in 2007; both strains have proved to be genetically different [9]. Their original reference numbers are ABL-99/28 and ABL-07/58, respectively, in the Culture Collection of the Edible and Medicinal activé es aprè s stockage en comparaison avec le contrôle ainsi que la transformation du substrat, comme dé crit par les ratios d'aromaticité et d'humification calculé s à partir des donné es de RMN.…”
Section: The Fungal Strainsmentioning
confidence: 99%